(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Terrorism continues to be an urgent international problem, despite a slight decrease in terrorist activity after the military defeat of ISIS * in Syria and Iraq. This article attempts to examine the main areas of the UN counter-terrorist activities in the 2000s. The authors have revealed the importance of the Global Counter-Terrorism Strategy for intensifying the combat against global terrorism. The content of the institutional reform of the system of UN organizations that counter terrorism is described in detail. A special focus is on the tasks and functions of the Counter-Terrorism Committee, the Counter-Terrorism Center, and the UN Counter-Terrorism Office. Special attention is paid to the analysis of some unresolved problems in the activities of the UN as the center of the combat against terrorism in the world.